UPAYA PROMOTIF, PREVENTIF DAN DETEKSI DINI ANEMIA PADA REMAJA di SMPN 02 BANGKALAN - Riyadatus Soliha; Norma Farizah Fahmi (STIKES NGUDIA HUSADA MADURA, 2020)
Anemia is a state of iron deficiency, where anemia can affect anyone, including adolescents who are still at an early age. Based on the World Health Organization (WHO) 2010 states that of all adolescents in developing countries the prevalence of anemia in adolescent girls is 53.7%. The results of the Basic Health Research (RISKESDAS) in 2013, showed that the prevalence of anemia in Indonesia was 21.7%. Anemia patients aged 5-14 years were 26.4% and patients aged 15-24 years were 18.4% (Ministry of Health, Republic of Indonesia, 2014). Based on a survey through interviews with counseling teachers at SMPN 02 Bangkalan, 5% of young women tended to leave the first day of menstruation because they felt dizzy and had dysmenorrhea and 13% rested in the UKS room, especially on the first day of menstruation. This shows the tendency of young women to experience dizziness and discomfort caused by the large amount of blood that comes out during menstruation, so the possibility of experiencing anemia is very high. The method used to carry out community service is by collecting data on the number of grade VII adolescents at SMPN 02 Bangkalan. There were 60 female adolescents of grade VII at SMPN 02 Bangkalan, only 24 students who showed signs and symptoms of anemia who participated in the training and early detection of anemia. During the seventh grade teenage girls activity, they were very enthusiastic about the material presented. There were 24 students with the results that 58.3% were not anemic and 41.7% were anemic